Field Test on Performance of an Air Source Heat Pump System Using Novel Gravity-Driven Radiators as Indoor Heating Terminal - Jia, Jie; Zhou, Xuan; Feng, Wei; Cheng, Yuanda; Tian, Qi; Li, Fenglei; Chen, Yanjun; Lee, W.L. (Frontiers in Energy Research, 2021)
The simultaneous need for energy efficiency and indoor comfort may not be met by existing air source heat pump (ASHP) technology. This study contributes to the literature by proposing a novel gravity-driven radiator for use as the indoor heating terminal of ASHPs, aiming to provide an acceptable level of indoor comfort with improved energy efficiency. A field test was performed to examine the operational characteristics and performance of the proposed system. It was found that the proposed radiator has a rapid thermal response, which helps to reduce the thermal mass of a heat pump heating system. The proposed system can create a stable and uniform indoor environment with a measured air diffusion performance index of 80%. The first and second law efficiency of the proposed system was also assessed based on the test data. It was found that the system’s first law efficiency is 42.5% higher than the hydraulic-based system. In terms of second law efficiency, the compressor contributes the most to the overall exergy loss of the system. An increase in the outdoor temperature can improve the system’s exergy performance. The exergy efficiency of the proposed system varies between 35.02% and 38.93% in the test period. The above findings confirmed that the proposed system can create a comfort indoor environment with rather high energy efficiency, making it a promising solution for space heating in the building industry.